Strategic Adaptation in Islamic Education Quality Management: Navigating Social Developments for Sustainable Educational Outcomes - Durotun Nisa; Siti Aimah (Al-Qalam Institue, 2024)
The aim of this study is to provide sustainable solutions in adaptation strategies in Islamic education management in dealing with social controversies. This study is based on the importance of adaptive management in improving the quality of education from social and technological progress. With a research design using qualitative methods and a case study approach. Data collection techniques in this study used observation, interviews with several informants, and documentation. The data analysis technique in this study used the Milles and Hubarman model, namely an interactive model including data reduction, data presentation, and drawing conclusions. The results of the study show that inclusive curriculum is designed to accommodate social and cultural diversity. Digital technology is used to enrich students' learning experiences, provide wider access to educational resources, and enable a more flexible and adaptive learning process. The application of a continuous evaluation model ensures that the assessment of the quality of education is carried out continuously by involving various school communities. These findings emphasize the importance of adapting inclusive and technology-based education strategies to ensure the relevance and quality of education amidst ever-evolving social dynamics.